(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
According to Acharya Kashyapa, Aahara is Mahabheshaja. Ayurveda is an untapped source of vast information about nutrition providing foods, drinks and regimen. There are healthier and effective replacements for the health supplements available in the market. Mudga is a common pulse found in almost every Indian household is fortified with Shatavari which is very well known for its balya rasayana action In this study Palalam (Ladoo) having reference in Bhavaprakasha Nighantu Kritaanavarga / 132 is made with modifications using Mudga, Shatavari and Tugaksheeri. Formulation, standardization, nutritional analysis, shelf life analysis, sensory tests of Mudga Shatavari Palalam is done to confirm its efficacy as a health supplement. All the tests were found to be satisfactory. The nutritional values of the product showed that it contains higher amount of nutrition, energy, proteins, dietary fiber, vitamin A, vitamin C, calcium, iron and has lower saturated fats, sodium and cholesterol. The Mudga Shatavari Ladoo was found to be fit for consumption, highly palatable and nutritive. Two servings of the product provide a person with 25% of the required daily nutrition. It can be given as a weight supplement to underweight children, lactating mothers, senior citizens, growing children and those having nutritional deficiency disorders and all others in general to improve immunity and to augment the nutrition from their diet. This formulation can also be used in the form of granules, biscuits etc as required. It can also be provided as part of mid-day meals in schools to improve the nutrition in children.